Distribution and abundance of aerobic anoxygenic phototrophic bacteria in the tropical coastal waters of Gunungkidul, Yogyakarta, Indonesia - Victor Aprilyanto; Langkah Sembiring; Tjut Sugandawaty Djohan (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Aprilyanto V, Sembiring L, Djohan TS. 2020. Distribution and abundance of aerobic anoxygenic phototrophic bacteria in the tropical coastal waters of Gunungkidul, Yogyakarta, Indonesia. Biodiversitas 21: 5506-5513. Aerobic anoxygenic phototroph (AAP) is a community of bacteria capable of performing anoxygenic photosynthesis in the presence of oxygen. AAP abundance in most oceanic regions signals its ecological importance in marine microbial loop. This study was conducted to reveal the distribution and abundance of AAP in Siung coast, Gunungkidul, Yogyakarta, Indonesia. Total bacterioplankton and AAP were enumerated using acridine orange direct count (AODC) and real-time quantitative PCR (qPCR), respectively. Several water physicochemical parameters as well as dissolved nitrate, ammonium, phosphate, and sulfate were also measured. The results showed that total bacterioplankton was distributed thoroughly in the water column with abundance ranging from 2.5×104 to 3.5×104 cells/mL. Within this total bacterioplankton, AAP ranged from 3.83×102 –7.48×102 cells/mL, comprising about 1% to ~2.5%. Inorganic nutrient concentration, mainly nitrate and phosphate were thought to be the regulating factors to the distribution and abundance of both communities. In conclusion, AAP comprises a relatively low portion of the total bacterioplankton community in the tropical coastal water in Gunungkidul, Yogyakarta.